Dukungan Manajemen Puncak Memoderasi Keterlibatan Pengguna dan Kemampuan Pengguna pada Kinerja SIA DISPERINDAG Provinsi Bali - Trenida, I Putu Gede Tata; Dwirandra, A.A. Ngurah Bagus (E-Jurnal Akuntansi, 2018)
The use of computerized accounting information systems can assist in the processing of corporate data so that the data will produce an information that can be useful for the company. The purpose of this study is to determine the effect of user involvement, user ability and top management support on the performance of accounting information system at the Dinas Perindutrian dan Perdagangan of Bali Province. This study took a sample of all users of Sistem Informasi Pengelolaan Keuangan Daerah (SIPKD) at Dinas Perindustrian dan Perdagangan Bali Province based on non-probability sampling method with purposive sampling technique as much as 40 sampling. Data collection was done by survey method. Analytical techniques in this study using multiple linear regression analysis and Moderating Regression Analysis (MRA). The results of this study indicate that user involvement has positive implications on the performance of Accounting Information Systems and the ability of users to have a positive implication on the performance of Accounting Information Systems. The result of Moderating Regression Analysis (MRA) shows that Peak Management Support strengthens the influence of User Involvement on Accounting Information System Performance while Top Management Support is unable to moderate User Ability to Accounting Information System Performance.